Factors, Perceptions and Beliefs Associated with Inappropriate Antibiotic Prescribing in German Primary Dental Care: A Qualitative Study - Böhmer, Femke; Hornung, Anne; Burmeister, Ulrike; Köchling, Anna; Altiner, Attila; Lang, Hermann; Löffler, Christin (Antibiotics (Basel), 2021)
Dentists account for up to 10% of all prescribed antibiotics in primary care, with up to 80% being inappropriate. Targeted approaches to change prescription behavior are scarce. This study aimed at identifying specific barriers and facilitators for prudent antibiotic use in German dentistry by using qualitative methods. Nine in-depth interviews and two focus group discussions with another nine dentists were conducted and analyzed thematically. Dentists described being conflicted by the discordance of available treatment time and the necessity of thorough therapy. Lacking the opportunity of follow-up led to uncertainty. Dentists felt a lack of medical competency concerning prophylaxis for infectious endocarditis. A lack of empowerment to make therapeutic decisions interfered with guideline-conformity. The communication with fellow physicians is conflictual and improvement was wished for. In consequence, dentists felt pressure by potential medico-legal liability. Patients demanding quick and easy pain relief put extra strain on the interviewed dentists. Our hypotheses concord with preliminary data, mainly from the UK, but highlighted specifically medico-legal concerns and interprofessional communication as even greater barriers as described before. Tailored interventional concepts based on our findings may have the potential to lower antibiotic prescriptions in German primary dental care.